Mobile learning in Malaysia: advantages and problems - Buntat, Y. (American Scientific Publishers, 2016)
Technology offers educators more effective and efficient ways to deliver knowledge. In this paper, we analyzed the benefits and challenges in implementing one type of technology, namely, Mobile Learning or M-Learning. A total of 10 downloaded journal articles published between 2002 and 2007 were reviewed. The results are discussed in terms of education and mobile technology, advantages of M-Learning in Education and problems in Integrating M-Learning in Education. Finally, future interventional studies are discussed.